A combined movement and story-telling intervention enhances motor competence and language ability in pre-schoolers to a greater extent than movement or story-telling alone. (February 2019) - Duncan, Michael; Cunningham, Anna; Eyre, Emma
This study examined the effect of a six week combined movement and story-telling intervention on motor competence and naming vocabulary in British pre-schoolers. Using a cluster randomised design, three pre-school classes were allocated to one of a combined movement and story-telling intervention ( n = 22), or a movement only ( n = 25) or story-telling only ( n = 27) intervention. Motor competence and language ability were assessed pre, post and eight weeks post intervention. Results from repeated measures ANOVA indicated significantly greater improvement in both motor competence and language ability pre to post intervention for the combined movement and story-telling group compared to the movement only or story-telling only groups. However, for the period post intervention to eight weeks post intervention the magnitude of change for motor competence and language ability was significant for all groups and similar in magnitude. The results of this study demonstrate the efficacy of combining movement and story-telling, over movement or story-telling alone, to benefit both motor competence and language ability in pre-schoolers. Combining both movement and story-telling appears to offer synergistic benefits in relation to physical and communication development, which are critical for good development in the early years.